Cash Wakaf Cash Waqf Behavior Supports Mental Health And Community Economy - Raden Ayu Ritawati; Raden Ayu Erika Septiana (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2023)
Cash waqf is the main potential in driving people's economic behavior. Its presence is also a solution in overcoming all mental health and economic problems of the ummah. Various Muslim countries in the world have implemented the potential of this cash waqf to overcome various healthy dan economic problems. Utilization of cash waqf can be carried out both productively and non-productively in various interests for the healthy and welfare of the community in general. Nazhir's role is central in cash waqf. The nature of cash waqf is not an obligation. Money as a basic asset (ashal/mauquf alaih) cannot be reduced or used up. Money must be transferred into productive assets that flow many benefits in a sustainable manner. This qualitative research seeks to provide a descriptive discourse on the application of contemporary fiqh. Where cash waqf can be managed with productive investment schemes such as mudharabah, musyarakah, ijârah and murabaha. All of this with the intention of profitably benefiting both parties. Then this profit will be used for the mental health and benefit of society at large while maintaining the basic value of the waqf property. While non-productive management can be carried out by constructing buildings/buildings as socio-religious infrastructure, such as places of worship, educational facilities, health, plantations, fisheries and other social facilities. While the management of financial services can be collaborated with other public financial sources such as the use of zakat, infaq and alms funds whose management is utilized for the benefit of increasing the welfare of the community in general.